Operation strategy and effect analysis of photovoltaic-energy storage system for single residential buildings under different electricity price models - LIU Xinyang; ZHANG Weirong; DENG Gaofeng; WANG Zhichao (Xi'an Gongcheng Daxue xuebao)
To understand the operational strategies and effects of photovoltaic-energy storage systems in standalone residential buildings under different electricity pricing modes, a model was developed for the electricity consumption of sample buildings and the power generation of photovoltaic systems. Two operational strategies, namely regular operation mode and mixed operation mode, were developed for photovoltaic-energy storage systems under two scenarios: tiered electricity pricing and time of use electricity pricing. Subsequently, the economic indicators net present value (NPV) and self consumption rate (SC) of the photovoltaic-energy storage system for single family residential buildings were analyzed for four energy storage unit prices ranging from 1 000 to 2 500 yuan/(kW· h) as the energy storage capacity increased. The results show that the larger the installed capacity of photovoltaic, the higher the initial NPV value. In the conventional operating mode, the self consumption rate of photovoltaic systems with different installed capacities gradually increases with the increase of energy storage capacity, while in the mixed operating mode, the self absorption rate basically does not change with the increase of energy storage capacity. In both operating modes, the optimal energy storage capacity considering only economy is located at the highest point of the NPV curve, and different photovoltaic installed capacities will result in different initial values and rankings of NPV.